Code-to-code comparisons of lattice physics calculations for thorium-augmented and thorium-based fuels in pressure tube heavy water reactors. (May 2017) - Colton, A.; Dugal, C.; Bromley, B.P.; Yan, H.
Highlights: The 2D lattice physics code WIMS-AECL was compared against MCNP using ENDF/B-VII.0. Fuels containing mixtures of PuO2, NUO2, LEUO2, ThO2 and 233 UO2 were modelled. 37-Element and 35-element bundle geometries for PT-HWR were considered. k-inf, LER and CVR agree well for NUO2, biases appear for (PuO2 /ThO2 ), (LEUO2 /ThO2 ). 89-Group fluxes were calculated and overall show a growing discrepancy with burnup. Abstract: Code-to-code comparisons of lattice physics calculations were made for a series of fuels that could potentially be used in a conventional 700-MWe class pressure tube heavy water reactor to improve the sustainability of the fuel cycle. Studies were performed for natural uranium, slightly enriched uranium and thorium-based fuels containing low enriched uranium, reactor grade plutonium, or 233 UO2 as the initial fissile driver. The collision probabilities lattice code WIMS-AECL was compared to the stochastic code MCNP using the ENDF/B-VII.0 nuclear data library. Specific parameters that were studied between models include k-infinity, coolant void reactivity, 89-group cell averaged fluence, and ring-by-ring linear element ratings. The calculations performed have demonstrated that physics parameters estimated by WIMS-AECL are consistent with MCNP, especially for fuel where the main fissile component is uranium-based.